Silver nanoparticles: Toxicity and inhibitory effects against Aflatoxins - Ackova, D G; Tatjana, K P (Plant Science Today, 2025)
Among the numerous nanomaterials, metal nanoparticles, like silver nanoparticles (AgNPs), are the most employed. Significant focus has been given to their dual role due to their versatile properties. Beneficial, on the one side, as potent antimicrobial properties determine different applications in medicine, agriculture, and food safety, to potentially harmful on the other side. Mycotoxins, secondary metabolites produced by toxigenic strains of fungi, are highly toxic substances recognized for their influence on processes of mutagenesis and carcinogenesis, hepatotoxicity, immunosuppression and estrogenic properties in animals and humans, posing severe threats to health through contaminated food and feed. Thus, this paper explores the toxicity mechanisms of AgNPs and their inhibitory effects on aflatoxins, a class of mycotoxins produced mostly by Aspergillus species that pose significant health risks. The interaction between AgNPs and aflatoxins is examined, highlighting the potential of AgNPs in mitigating aflatoxin contamination. The article gives a summary of the synthesis, properties, and dual roles of AgNPs in the toxicity and inhibition of aflatoxins, concentrating on their possible uses and safety concerns at the end. It is found that elements affect AgNP’s toxicity, like particle solubility, surface area, surface charge, size, concentration, formulation, tendency to agglomerate, and exposure duration. Therefore, assessing the safe levels of AgNP exposure and developing guidelines for their use in different fields are crucial for minimizing the risks. It can be summarized that the biosynthesized AgNPs generated through green synthesis, owing to their biocompatibility and low toxicity, could be applied in harmless concentrations as strong antifungals and anti-mycotoxins. This can offer significant potential for enhancing food safety due to their strong antimicrobial properties, which can inhibit the growth of foodborne pathogens and extend shelf life. However, the potential for nanoparticle migration into food must be considered, which raises critical concerns about human health, regulatory challenges, and environmental impact.